Recent advances in biodegradable biosensors for biomedical and environmental applications - Akkad, Haya; Kececi, Kaan; Ahlatcioglu Ozerol, Esma (TAYLOR & FRANCIS LTD, 2026)
Biodegradable biosensors represent a transformative advancement in sustainable sensing technology, offering an environmentally friendly and biocompatible alternative to traditional sensors. This review examines recent advancements, material innovations, degradation mechanisms, and application areas of biodegradable biosensors within the biomedical and environmental sectors. Natural and synthetic biodegradable polymers, such as chitosan, silk fibroin, alginate, PLA, PLGA, and PVA, are assessed for their functional contributions to sensing platforms. Applications, ranging from implantable cardiovascular and neural sensors to soil nutrient monitors and gas detectors, are detailed with corresponding performance data. Although challenges related to signal stability, integration, and long-term operation persist, future research emphasizes multifunctionality, wireless communication, energy autonomy, and AI-driven diagnostics. This review highlights the potential of biodegradable biosensors to transform health monitoring, environmental assessment, and personalized medicine by aligning technological functionality with principles of sustainability.
Keywords: Biosensors; biodegradable; biomedical; environmental; biomaterials; DEGRADATION; ALGINATE; POLYMERS; CHITOSAN; HYDROGEL; SENSORS; Engineering; Materials Science; Polymer Science